A Contrastive Genre-Based Approach to the Rhetorical Structure and Use of Interactional Metadiscourse in the Results and Discussion Section of Food Science & Technology Research Articles - del Saz-Rubio, Milagros (Miscelánea: A Journal of English and American Studies, 2019)
This paper describes a genre-based exploration of the rhetorical structure and use of interpersonal metadiscourse features in the Results and Discussion sections of 32 research articles written in English from the discipline of Food Science & Technology. The rhetorical moves and steps enacted in this section are first looked into. Following this, I have quantitatively assessed the researchers’ use of some interactional metadiscoursal units, drawing on Hyland’s framework (2005a, 2005b). As the corpus of analysis is made up of 16 papers authored by English L1 researchers, while another 16 have been written by Spanish researchers with English as their L2, it is also my aim to account for any differences with regard to the presence and frequency of use of the different moves/steps identified, and of the interactional metadiscoursal features selected for analysis in each of the two sub-corpora. Possible cross-cultural variations identified in the L1 and L2 corpus will be discussed. Findings indicate that results are presented and discussed mainly through obligatory Moves 2 and 3, and, to a lesser extent, Move 1. This exploratory approach has shown statistically significant differences for the categories of hedges and authorial presence, making them the strategies most often deployed by researchers with English as their L1.